Elimination of power divergences in consistent model for spinless and high-spin particle interactions - Kulish, Yu.V.; Rybachuk, E.V. (Вопросы атомной науки и техники, 2007)
The currents for the interaction of the massive high-spin boson (J≥1) with two spinless particles are derived. These currents obey the theorem on currents and fields as well as the theorem on current asymptotics. In one-loop approximation the contributions of high-spin boson to the self-energy operator for a spinless particle are calculated. It is shown that in one loop approximation the high-spin boson contributions for any spin J and mass lead to finite self-energy operators of spinless-particle. Одержано струми взаємодій масивних високоспінових бозонів (J≥1) з двома безспіновими частинками. Ці струми задовольняють теоремі про поля та струми, а також теоремі про асимптотику струмів. В однопетльовому наближенні показано, що внески високоспінових бозонів при довільних спіні J і масі дають скінчений оператор власної енергії безспінової частинки. Получены токи взаимодействия массивного высокоспинового бозона (J≥1) с двумя бесспиновыми частицами. Эти токи удовлетворяют теореме о полях и токах, а также теореме об асимптотике токов. В однопетлевом приближении показано, что вклады высокоспинового бозона при любых массе и спине дают конечный оператор собственной энергии бесспиновой частицы.